1990
DOI: 10.1017/s0022029900029460
|View full text |Cite
|
Sign up to set email alerts
|

Variation with season and lactation of plasmin and plasminogen concentrations in Montbeliard cows' milk

Abstract: Plasmin and plasminogen were determined monthly over a one year period in samples of bulk and herd milks from Montbeliard cows. Montbeliard milk showed a high content of plasmin and plasminogen in comparison with milk from other breeds. In bulk milk, the plasmin activity reached a minimum in September (015/tg/ml milk) and a maximum in June (032/ig/ml milk). The annual mean concentration was 0-23 /ig/ml milk. The plasminogen content varied around a value of 1-28 /tg/ml milk, with a marked decrease in September … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
12
0
1

Year Published

1994
1994
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 31 publications
4
12
0
1
Order By: Relevance
“…Similar changes in milk composition have been reported in other countries, e.g., Australia (Auldist et al, 1996;Walker, Dunschea, & Doyle, 2004), Canada (Kroeker, Ng-Kwai-Hang, Hayes, & Moxley, 1985), France (Martin & Coulon, 1995), New Zealand (Auldist, Walsh, & Thomson, 1998;Nicholas, Auldist, Molan, Stelwagen, & Prosser, 2002) and the UK (Banks & Tamime, 1987). Factors contributing to these changes include the combined effects of differences in stage of lactation (which alters the udder physiology and metabolism), plane of nutrition (especially for cows fed on pasture grass), somatic cell count and season (Benslimane, Dognin-Bergeret, Berdague, & Gaudemer, 1990;Givens, Moss, & Adamson, 1993;Hurley & Ford, 2003;Nicholas et al, 2002).…”
Section: Introductionsupporting
confidence: 55%
“…Similar changes in milk composition have been reported in other countries, e.g., Australia (Auldist et al, 1996;Walker, Dunschea, & Doyle, 2004), Canada (Kroeker, Ng-Kwai-Hang, Hayes, & Moxley, 1985), France (Martin & Coulon, 1995), New Zealand (Auldist, Walsh, & Thomson, 1998;Nicholas, Auldist, Molan, Stelwagen, & Prosser, 2002) and the UK (Banks & Tamime, 1987). Factors contributing to these changes include the combined effects of differences in stage of lactation (which alters the udder physiology and metabolism), plane of nutrition (especially for cows fed on pasture grass), somatic cell count and season (Benslimane, Dognin-Bergeret, Berdague, & Gaudemer, 1990;Givens, Moss, & Adamson, 1993;Hurley & Ford, 2003;Nicholas et al, 2002).…”
Section: Introductionsupporting
confidence: 55%
“…The concentrations assayed in herd milks with this microparticle-enhanced nephelometric immunoassay ranged from 1.1 to 4.9 mg I" 1 . They were close to those previously reported using another immunological method (2.6-4.8 mg I" 1 by Collin et al, 1988) but were often slightly higher than the levels obtained by the spectrophotometric methods based on the measurement of bPl activity (0.2-2.8 mg I" 1 ; Richardson & Pearce, 1981;Korycka-Dahl et al, 1983;Rollema et al, 1983;Benslimane et al, 1990). Month-bymonth comparison of the results of this study indicated a possible seasonal variation of the bPIg concentration in milk.…”
Section: Discussionsupporting
confidence: 88%
“…Month-bymonth comparison of the results of this study indicated a possible seasonal variation of the bPIg concentration in milk. Such a variation has been already observed, with an increase of bPl activity in the summer (Benslimane et al, 1990). However, this seasonal variation could also be the consequence of the stage of lactation, milk bPIg levels reaching 12 mg 1~ ' and even 30 mg I" 1 (Kaartinen & Pyörälä, 1989;Dupont et al, 1995) during early lactation.…”
Section: Discussionsupporting
confidence: 62%
“…This proteolysis is due to plasmin, whose activity increases in late lactation [11], especially when SCC are high [5]. Plasmin is certainly also involved in the texture differences noted between valley and mountain cheeses in Bugaud et al's trial [17] or between the north and south sides of the same pasture [16], as its activity was highly variable from one situation to another.…”
Section: Endogenous Enzymesmentioning
confidence: 99%